Renewing the Tradition: The theological project of James Alison - Kaplan, Grant (America, 2014)
James Alison belongs on any short list of the most important living Catholic theologians. He has met and perhaps exceeded the high expectations that arose from his first book, Knowing Jesus (1993), and his most substantial work of constructive theology, The Joy of Being Wrong: Original Sin Through E